Phytotherapy: A Systematic Review for the Treatment of Hypertension - Lachovicz, Rebeca (2025)
Approximately 10 million annual deaths may be associated with hypertension. Adverse effects and non-response to pharmacological treatment limit therapy to a significant proportion of patients; hence, treat- ment alternatives seem necessary. Our objective was to review data about the impact of herbal medicine on reducing blood pressure (BP) in prehypertensive and hypertensive patients. Methods: A systematic review was conducted (PRISMA guidelines), using PUBMED, SCOPUS, and WEB OF SCIENCE databases, without time restriction. The inclusion criteria were randomised controlled trials and quasi-experimental studies in humans focusing antihypertensive effect of phytotherapeutics: Allium sativum, Apium graveolens, Nigella sativa, Panax ginseng, and Hibiscus sabdariffa on BP in adults with prehypertension or hypertension. The exclusion criteria were the usage of combined medicinal plants. Data about systolic and diastolic BP differences before and after phytotherapy were extracted manually and summarised. The risk of bias was assessed using the JBI tool. Results: Forty-five studies were selected (15 A sativum, 4 A graveolens, 4 N sativa, 9 P ginseng, and 13 H sabdariffa). Antihypertensive effect was observed for A sativum systolic and diastolic BP (−18.1/−9 mmHg), A graveolens (−37.9/−15.4 mmHg), N sativa (−11.8/−8.8 mmHg), P ginseng (−17.4/−7.1 mmHg), and H sabdariffa (−61.4/−66.2 mmHg). Discussion/Conclusions: Herbal medicines can reduce high BP levels in prehypertension and hypertension, when used alone or together with lifestyle changes or antihypertensive drugs. Results interpretation is crucial, given the studies quality variation and the discrepancies. More consistent clinical studies in humans are needed to accurately determine efficacy and safety in the treatment of hypertension.